African animal genetic resources: Their characterisation, conservation and utilisation. Proceedings of the research planning workshop - Rege, J.E.O.; Lipner, M.E. (International Livestock Centre for Africa, 1992)
Addresses different papers presented on the workshop organised by ILCA, as part of the research planning process on a project of characterisation, conservation and utilization of Africa's indigenous animal genetic resources. In taking on this challenging task, ILCA recognised that it could not succeed without substantial collaboration with NARS colleagues. However, it also recognised the need to work out standard characterisation methodology and to outline the implementation process. Workshop participants reached the consensus that this project was timely and that activities should be initiated to document Africa's animal genetic resources, with a view to developing strategies for their conservation and sustainable utilisation. While stressing the importance of breed characterisation, participants reiterated that those breeds identified as currently endangered should be conserved even if their value is not presently apparent. Considerable attention was given to development of experimental designs which would optimise collection of data on population dynamics, physical characteristics and phenotypic and genetic parameters of biological performance traits.